A educação ambiental como ferramenta de conscientização no contexto da crise hídrica: um mapeamento preciso de necessidades, desnecessidades e direcionamento sustentável em um bairro do município de São Carlos - SP - Silva, Daizi (Universidade Federal de São Carlos, 2023)
This study aims to use Environmental Education (EE) as a tool for raising awareness in the context of the water crisis, by producing a detailed mapping of the needs and lack of needs in a neighborhood in the city of São Carlos-SP. The purpose is to guide individuals to adopt more sustainable practices, investigate the main causes of water waste and analyze the resulting environmental impacts, highlighting the relevance of the problem. The research collected data on waste and water management, which were analyzed with the aim of contributing to minimizing the impacts generated by the normalization of existing behaviors. The study is based on the historical trajectory of the topic, which demonstrates the need to reduce waste and promote citizenship through actions that contribute to the formation of conscious and critical citizens, capable of developing social values ​​and resources for current and future generations. In this sense, EE presents itself as a fundamental tool for understanding the interactions between society, education and the environment. The concepts presented in the study are based on the understanding of exploratory data analyzed in light of the information and assumptions studied. The instrument used for data collection was semi-structured interviews, in which 30 individuals were interviewed, divided into three categories: university students (A), traders (B) and non-university students (C). The research adopted an exploratory and descriptive approach to understand the discrepancy in the data and explore EE as an instrument that contributes to minimizing the consequences resulting from human activities. The results of the research point to the challenge of raising awareness among the population about the importance of saving water, since a significant proportion of the interviewees consume an amount above the average recommended by the UN. However, it was possible to identify that some of the interviewees already adopt sustainable practices, such as water reuse, indicating the existence of a potential for the adoption of more sustainable practices. This information can be used to develop educational projects and to promote changes in habits in favor of the rational use of water.
Environmental education as a tool for raising awareness in the context of the water crisis: a precise mapping of needs, lack of needs and sustainable direction in a neighborhood in the municipality of São Carlos - SP
Keywords: Educação ambiental; Crise hídrica; Práticas sustentáveis; Desperdício de água; CIENCIAS BIOLOGICAS::BIOLOGIA GERAL